Does Corporate Governance Increase Related Party Transaction Disclosure In Indonesia? - Amrie Firmansyah; Pria Aji Pamungkas; Fardan Ma’ruf Zainuddin (EAJ (Economic and Accounting Journal), 2021)
The purpose of this study is to examine the effect of corporate governance (audit committee, institutional ownership, managerial ownership, and independent commissioners) on Related Party Transaction Disclosure. The data employed in this study is secondary data, financial statements from manufacturing sector companies listed on the Indonesia Stock Exchange from 2016 up to 2019. Based on the purposive sampling conducted, companies that meet the criteria in this study are 40 companies, so that the total sample is 160 observations. This study uses panel data regression analysis. This study finds that the independent commissioner has a positive effect on Related Party Transaction Disclosure. Meanwhile, the audit committee, managerial ownership, and institutional ownership do not affect Related Party Transaction Disclosure. This research indicates that the Indonesian Financial Services Authority (OJK) should supervise and tighten the rules for Indonesia listed companies, especially regarding the audit committee's or independent commissioner's requirements in listed companies.